Impact of educational process innovation on the satisfaction of higher education students in Ecuador - Danny Xavier Arevalo Avecillas; Rober Anibal Luciano Alipio; Carmen Paola Padilla Lozano; Manuel Esteban Arevalo Avecillas; Hugo Daniel García Juárez (Knowledge & Performance Management)
Type of the article: Research Article Innovation in educational processes is a key factor for student satisfaction, as it guarantees quality, academic retention, and institutional competitiveness in higher education. This study aimed to evaluate the impact of innovation in educational processes on student satisfaction in higher education institutions in Ecuador. A quantitative approach was used, with a non-experimental, cross-sectional, and explanatory design. The sample consisted of 388 university students from Guayaquil, one of the largest cities in Ecuador, who completed a structured, online, Likert-scale questionnaire after providing their informed consent between September and October 2024. Innovation in educational processes was conceptualized through two core dimensions: structure and process management. Student satisfaction was analyzed through three dimensions: trust and security, tangible elements, and motivation to participate. To ensure the validity and reliability of the constructs, exploratory and confirmatory factor analyses supported by structural equation modeling (SEM) were conducted using SPSS version 26 and AMOS version 22. The results showed that process structure had a significant effect on trust and security (β = 0.65, p < 0.001), tangible elements (β = 0.37, p < 0.001), and motivation (β = 0.77, p < 0.001). Similarly, process management significantly influenced trust and security (β = 0.65, p < 0.001), tangible elements (β = 0.62, p < 0.001), and motivation (β = 0.72, p < 0.001). In conclusion, innovation strategies in educational processes substantially affect student satisfaction, highlighting the importance of effective and progressive academic management in Ecuadorian higher education.